Droughts and corruption - Daniela Wenzel; Ralf Dewenter (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2018)
Natural disasters are a challenge for good governance - this is the result of recent research investigating the effects of natural disasters on one important antagonistic force to good governance, public corruption. However, a specific analysis of droughts is so far neglected in this young strand of the literature. This paper fills that gap by analysing the short- and long-term influence of droughts on corruption within a unified panel estimation approach for 122 countries during the years 1985 to 2013. Relying on a meteorological drought index, we show that higher drought exposure is followed by increases in corruption. This effect holds true for subgroups of poor and rich countries although its timing and intensity is different. In addition, we identify drought-induced corruption as a phenomenon of countries yielding high per capita income in the agricultural sector.
Keywords: D73; E02; Q54; Q56; 330; Drought; Natural Disasters; Public Sector Corruption; Institutions; Economic Development